Peran Bhabinkamtibmas Melalui Penyuluhan Untuk Mengatasi Tindak Pidana Curanmor Roda Dua Di Polsek Ciamis - Nadapdap, Frans Billy (Police Studies Review, 2020)
This research is motivated by the increasing number of criminal acts of theft of two-wheeled motor vehicles in Ciamis District. The high level of community activities in Ciamis Subdistrict makes the crime that occurred to be high too. Writing this thesis uses a qualitative approach to the type of descriptive research. Data collection techniques with interviews, observations, and document review. There are primary and secondary data sources and the theories used to analyze are role theory and management theory. The results of the study found that the role of Bhabinkamtibmas in preventing criminal acts of two-wheeled carburetor was carried out through coaching conducted to the Bhabinkamtibmas. While the efforts made by Bhabinkamtibmas through door to door counseling activities. There are factors that influence Bhabinkamtibmas in carrying out their duties, namely internal factors consisting of human resource factors, facilities and infrastructure factors, and budget factors while external factors come from the community itself. Based on the discussion of the study the authors advise leaders to conduct analysis and evaluation of Bhabinkamtibmas personnel and have a standard for assessing members of Bhabinkamtibmas, emphasizing the provision of material to the public regarding the theft of two-wheeled motorized vehicles, improving suggestions and infrastructure owned by the Ciamis Police Station, and provide rewards and punishment to members of Bhabinkamtibmas as motivating for work.